Agronomist Response to the Application of Young Coconut Skin Waste Biochar to Soybean Plants (Glycine max L.) - Helmi, Helmi (Jurnal Sains Riset, 2025)
ABSTRACTThe purpose of the study was to determine the agronomic response of biochar distribution of young coconut bark waste to the growth and yield of soybean plants. This research was carried out at the experimental garden of the Faculty of Agriculture, Jabal Ghafur University from April to July 2024. This study used a Non-Factorial Group Random Design (RAK) of 3 treatments with 3 replicates. The biochar factor of young coconut waste (B) consists of 3 levels, namely: B0 0 tons ha-1, B1 20 tons ha-1, and B2 30 tons ha-1. The results showed that the effect of young coconut waste biochar had a very real effect on the parameters of pod count, root length, wet pod weight, weight 100 beans and production per ha, but the effect was not real but did not have a real effect on other parameters. The best treatment is found in the treatment of B1 20 tons ha-1.